2008
DOI: 10.3346/jkms.2008.23.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Asian Dust Events on Respiratory Symptoms and Peak Expiratory Flow in Children with Mild Asthma

Abstract: The aim of this study was to investigate the possible adverse effects of Asian dust events on respiratory health in asthmatic children. Fifty-two children with mild asthma were studied for eight consecutive weeks in the spring of 2004 (March 8 to May 2). During the study period, five Asian dust days were identified; we included a lag period of two days following each of the events. Subjects recorded their respiratory symptom diaries and peak expiratory flow (PEF) twice daily during the study period; and they u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 20 publications
(28 reference statements)
0
41
0
1
Order By: Relevance
“…Other studies in Taiwan and in Korea indicated a statistically significant association between Asian dust events and daily pneumonia admissions one day after the event (Cheng et al, 2008). In addition, dust storms are impacting on the respiratory symptoms of patients with bronchial asthma (Park et al, 2005;Yoo et al, 2008). Moreover, studies done in other regions of the world have underlined two key points.…”
Section: Impacts Of Desert Dust On Human Healthmentioning
confidence: 99%
“…Other studies in Taiwan and in Korea indicated a statistically significant association between Asian dust events and daily pneumonia admissions one day after the event (Cheng et al, 2008). In addition, dust storms are impacting on the respiratory symptoms of patients with bronchial asthma (Park et al, 2005;Yoo et al, 2008). Moreover, studies done in other regions of the world have underlined two key points.…”
Section: Impacts Of Desert Dust On Human Healthmentioning
confidence: 99%
“…It can be expected that a short-duration dust storm taking place during a wet period may have little significant impact on health in downwind reach areas. Conversely, however, there is evidence that people are becoming more concerned about the possible adverse effects of dust because dust events have increased in magnitude and frequency (Yoo et al 2008). Many studies carried out in West Africa emphasise recent increases in desertification processes (e.g.…”
Section: Dust-health Relationship -Publication Datementioning
confidence: 99%
“…In one study, Saharan dust days (SDDs) were defined by combining light detection and ranging (LIDAR) observations and analyses from operational models (Mallone et al 2011). Finally, some studies used direct information from the Ministry of Special Agency about dust events Watanabe et al 2011;Yoo et al 2008).…”
Section: Dust-health Relationship -Publication Datementioning
confidence: 99%
See 1 more Smart Citation
“…These isolates belonged to either genus Bacillus or genus Streptococcus and were tentatively identified as B. 기존 국내에서의 황사에 대한 연구는 modeling을 통한 이동 경로 분석, 미세먼지의 농도, 화학적 조성 및 입자의 크기 분포, 호흡기 질환과의 관계에 관한 역학 조사 등에 관한 것이 다수를 차지하고 있다 (Lee et al, 2007;Park et al, 2008;Yoo et al, 2008). 국제적으로는 황사 먼지를 통한 미생물의 장거리 이동에 대한 여러 연구가 있다 (Ichinose et al, 2008;Iwasaka et al, 2009 …”
unclassified